Transportation of apical root canal after removal of calcium hydroxide when used as an intracanal medicament: An in vitro evaluation - Nurul-Ameen Inamdar; Salma H Mulla (Wolters Kluwer Medknow Publications, 2013)
Aim: To evaluate the incidence of apical root canal transportation after the removal of calcium hydroxide in straight and curved canals. Materials and Methods: Twenty maxillary central incisors (Group A) and twenty mandibular molars (Group B, mesiobuccal canal) were instrumented to the working length using #15 to #45 K-file and # 15 to #30 K-file, respectively. Post instrumentation digital images were taken with the corresponding final file inserted into the canal to the working length. The root canals were then filled with Calcium hydroxide paste using Lentulo spirals and the teeth incubated at 37°C for seven days. The calcium hydroxide paste was then removed up to the working length using a #45 file for group A and a pre curved #30 file for group B. Final digital images were taken with the file inserted into the canal to the working length. Post instrumentation and final digital images were superimposed to evaluate the incidence of transportation. Result: In Group A, no transportation was detected, whereas in Group B, 8 out of 20 canals showed apical transportation. Statistically significant differences were observed between Groups A and B ( P <0.05). Conclusion: Care should be taken when removing the calcium hydroxide paste from curved root canals to avoid transportation.